Grade 1 teachers’ experiences of supporting learners with Attention-deficit/Hyperactivity Disorder (ADHD) - De Villiers, Zandra (Cape Peninsula University of Technology, 2022)
Attention-deficit/hyperactivity disorder (ADHD) is a growing phenomenon that affects millions of learners worldwide (Fleur, 2018). Perold, Louw and Kleynhans (2010) as well as Schellack and Meyer (2016) report that the number of learners being diagnosed with ADHD in South Africa has increased. Thus, the Department of Basic Education (South Africa. Department of Education, 2001:55) emphasises that Foundation Phase learners (Grades R-3) should be prioritised for early identification of ADHD and support. The policy on Screening, Identification, Assessment and Support (SIAS document) stipulates that it is the teachers’ responsibility to support learners with barriers to learning and development, which includes learners displaying ADHD symptoms (South Africa. Department of Basic Education, 2014). However, despite the SIAS document’s emphasis on early identification and support, it seems there is a grey area, whereby teachers have observed learners in their mainstream Grade 1 classrooms who daily display ADHD symptoms. These learners, though, have not been formally diagnosed with ADHD but might be in the process of referral for further assessment, as recommended by the SIAS document (DBE, 2014). Hence, it is essential that Foundation Phase teachers, especially Grade 1 teachers, have the necessary knowledge, experience and beliefs to accommodate these learners in their classrooms. An increasing number of young learners display visible ADHD symptoms at a young age; as Grade 1 is the first grade of formal learning, this impacts the child’s future development in an extensive manner (Colomer et al., 2017; Pascual, Muñoz & Robres, 2017). There is concern about the gap in literature focusing on Grade 1 teachers’ experiences, knowledge, beliefs and perspectives in implementing support strategies to enhance the learning of Grade 1 learners with ADHD or displaying ADHD symptoms. This research study is guided by the principles of Bronfenbrenner’s bioecological model of human development and Feuerstein’s model of mediated learning experience. Hence, this study addresses the main research question: What are Grade 1 teachers’ experiences of supporting learners with ADHD? In addressing the above-stated main research question, an exploratory, interpretive, interactive, qualitative case study has been employed as the research methodology. The Adapted Interactive Qualitative Analysis method of Northcutt and McCoy (2004) has been utilised to collect rich data from 12 purposefully selected Grade 1 teachers participating in an unstructured open-ended focus group interview. During this interview, an interview framework depicting the themes and descriptive paragraphs was developed. The interview framework guided the further collection of data by interviewing six purposely selected Grade 1 teachers from the original focus group and visiting their classrooms to ensure an authentic understanding by the researcher of what is transpiring pedagogically. The rich and in-depth data collected was transcribed and analysed utilising Zhang and Wildemuth’s (2017) qualitative content analysis technique. Findings of this study indicate that Grade 1 teachers with diverse backgrounds and from various school contexts in the Western Cape are knowledgeable regarding ADHD symptoms. However, they are in dire need of in-service training and school visits to guide them on how to specifically accommodate and support the Grade 1 learner with ADHD symptoms. It is further found that despite the need for training, Grade 1 teachers are innovative and seek to improvise and create resources that specifically enhance the teaching and learning of Grade 1 learners displaying ADHD symptoms. Based on the data analysis of the focus group interview, individual interviews and school visit observations, recommendations focusing on various support strategies in assisting and supporting Grade 1 learners with ADHD or displaying ADHD symptoms were made. In conclusion, recommendations are made to Grade 1 role-players for supporting and addressing the needs of learners with ADHD.
Thesis (MEd)--Cape Peninsula University of Technology, 2022
Keywords: Hyperactive children -- Education; Attention-deficit disordered children -- Education; Attention-deficit hyperactivity disorder; Elementary school teachers; Classroom management; Effective teaching; Special education